HUMAN RESOURCE SOFT SKILLS DEVELOPMENT: A STRATEGIC APPROACH TO FACING THE CHALLENGES OF ERA 6.0 - Preti Salsa Nabila; Nur Hazmi Kaila; Moza Claudia; Wahyu Akbar (Proceeding International Conference on Islam and Civilization (ICONIC), 2026)
This study aims to analyze the importance of developing Human Resources (HR) Soft Skills to face the challenges of the 6.0 era. The rapid advancement of technology has transformed nearly every aspect of life, including business, industry, and education. In this technological era, Soft Skills have a positive impact by opening various job opportunities, especially with the rise of social media, SEO specialists, web developers, content creators, and other professions. However, developing Soft Skills faces several challenges, one of which is resistance. Therefore, HR must be developed to address the 6.0 era’s challenges, such as a fast-paced lifestyle and increasingly modern, sophisticated behaviors. In the workplace, employees must possess competent and high-quality Soft Skills, and the same applies in education. This study uses a qualitative descriptive method with a literature approach to provide an overview and insight into the importance of developing HR Soft Skills in the 6.0 era. Data is collected from various theoretical sources such as books, journals, and online publications discussing the development of HR Soft Skills in facing the 6.0 era’s challenges, including what those challenges are and strategies to overcome them. The findings emphasize that HR today must be developed in both Soft and Hard Skills, especially among Generation Z and Alpha, to face the challenges of this advanced technological era.